2023 Post-Election Adjustment Behaviour Among Undergraduates at Ignatius Ajuru University of Education: Implications for Counselling - Maclean PhD, Onisoya; Nwachukwu PhD, Konye (Researchparks Publishing, 2025)
This study investigates 2023 post-election adjustment behaviour among undergraduates at Ignatius Ajuru University of Education and its implications for counselling. The study was guided by three objectives, research questions and hypotheses. The study was anchored on the cognitive dissonance theory. A descriptive research design was employed for the study. The population of the study consisted of 2,160 400-level undergraduates from the Faculty of Education, at Ignatius Ajuru University of Education, with a Taro Yemen's informed sample size of 338 undergraduates. Data was collected using a 4-point Likert scale questionnaire. The questionnaire was validated and tested for reliability using Cronbach's alpha, with a coefficient of 0.85 indicating high internal consistency. The mean and standard deviation were used to answer the research questions, while the hypotheses were tested using t-tests at the 0.05 level of significance. The findings, among others, revealed that females showed higher levels of post-election adjustment behaviours compared to males. Furthermore, the hypothesis showed that there is a significant difference in the perceptions of undergraduates based on their gender in the post-election adjustment behaviours exhibited after the 2023 elections. Based on the findings, the study concluded that gender plays a crucial role in determining how undergraduates cope with post-election adjustments, with females demonstrating a greater tendency towards seeking social support and self-care. The counselling implications of these results suggest that tailored interventions may be more effective if they take into account gender differences in coping strategies, potentially leading to more successful outcomes for both male and female students during times of political stress.